2005
DOI: 10.1002/asna.200410352
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of Stephenson's Hα stars

Abstract: Abstract. Hitherto unstudied objects from Stephenson's list of Hα emission line objects at high galactic latitude were observed spectroscopically to prove their nature. 9 out of 11 objects show Hα in emission. Spectroscopy combined with photometric information indicates most of them being classical Be stars, while one object is a Post-AGB star and one a T-Tauri star. The classification of two objects, which are showing Hα in emission, is unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…A total of 206 candidates were identified on a series of ≈1300 5.2 × 5.2 degree red-sensitive objective prism plates acquired at a dispersion of 1000 Å/mm and a limiting magnitude ∼13. Subsequent spectroscopic follow-ups (Downes & Keyes 1988;Weaver & Hobson 1988;Maheswar, Manoj, & Bhatt 2003;Emprechtinger et al 2005) of the resultant catalog [StHA] have identified several T Tauri stars including a handful at high Galactic latitude such as StHA 18 in MBM 12. Kun (1992) conducted a deeper objective prism survey (to V ∼ 16) with the Schmidt telescope of Konkoly Observatory covering the MBM 23-44, 49, 50, 53, 54 and 55 molecular clouds which resulted in 100 candidate Hα emission-line stars.…”
Section: Hα Surveysmentioning
confidence: 99%
“…A total of 206 candidates were identified on a series of ≈1300 5.2 × 5.2 degree red-sensitive objective prism plates acquired at a dispersion of 1000 Å/mm and a limiting magnitude ∼13. Subsequent spectroscopic follow-ups (Downes & Keyes 1988;Weaver & Hobson 1988;Maheswar, Manoj, & Bhatt 2003;Emprechtinger et al 2005) of the resultant catalog [StHA] have identified several T Tauri stars including a handful at high Galactic latitude such as StHA 18 in MBM 12. Kun (1992) conducted a deeper objective prism survey (to V ∼ 16) with the Schmidt telescope of Konkoly Observatory covering the MBM 23-44, 49, 50, 53, 54 and 55 molecular clouds which resulted in 100 candidate Hα emission-line stars.…”
Section: Hα Surveysmentioning
confidence: 99%